Du récit de voyage romantique à l’essai méditerranéen : l’improbable dialogue entre Maurras et Camus - Etienne Maignan (Caliban: French Journal of English Studies)
The reception of Anthinéa written by Charles Maurras presents a great contrast to that of Noces and L’Été written by Albert Camus: the former has been relegated to oblivion (a carved text, unscrupulously caricatured, never seriously republished), while the latter has been hailed as a most influential literary production (by publishers, academic syllabi, etc.). We want to redeem the former from oblivion by showing what the latter owes to its predecessor, without denying the specificities that distinguish their authors. These two works have much in common: Mediterranean Sea places, landscapes, themes, and a longing for a sensitive and intimate relationship with things. Some sentences even echo one another, thus suggesting possible intertextual connections. This study contributes to the establishment of the Mediterranean essay as a genre.